Macro/microporous silk fibroin scaffolds with potential for articular cartilage and meniscus tissue engineering applications - Yan, Leping (2012)
This study describes the developmental physicochemical properties of silk fibroin scaffolds derived from high concentration aqueous silk fibroin solutions. The silk fibroin scaffolds were prepared with different initial concentrations (8%, 10%, 12% and 16% (wt%)) and obtained by combining the salt-leaching and freeze-drying methodologies. The results indicated that the antiparallel β-pleated sheet (silk-II) conformation was present in the silk fibroin scaffolds. All the scaffolds possessed macro/micro porous structure. Homogeneous porosity distribution was achieved in all the groups of samples. As the silk fibroin concentration increased from 8% to 16%, the mean porosity decreased from 90.8±0.9% to 79.8±0.3%, and the mean interconnectivity decreased from 97.4±0.5% to 92.3±1.3%. The mechanical properties of the scaffolds exhibited a concentration dependence. The dry state compressive modulus increased from 0.81±0.29 MPa to 15.14±1.70 MPa, and the wet state dynamic storage modulus increased around 20-30 folds at each testing frequencies when the silk fibroin concentration increased from 8% to 16%. The water-uptake ratio decreased by means of increasing silk fibroin concentration. The scaffolds present favorable stability as their structure integrity, morphology and mechanical properties were maintained after in vitro degradation for 30 days. Based on these results, the scaffolds developed in this study are herein proposed to be used in meniscus and cartilage tissue engineering scaffolding.